Novel genetically encoded fluorescent probes enable real-time detection of potassium in vitro and in vivo. Issue 1 (December 2017) - Bischof, Helmut; Rehberg, Markus; Stryeck, Sarah; Artinger, Katharina; Eroglu, Emrah; Waldeck-Weiermair, Markus; Gottschalk, Benjamin; Rost, Rene; Deak, Andras; Niedrist, Tobias; Vujic, Nemanja; Lindermuth, Hanna; et al.
Abstract Changes in intra- and extracellular potassium ion (K+ ) concentrations control many important cellular processes and related biological functions. However, our current understanding of the spatiotemporal patterns of physiological and pathological K+ changes is severely limited by the lack of practicable detection methods. We developed K+ -sensitive genetically encoded, Förster resonance energy transfer-(FRET) based probes, called GEPIIs, which enable quantitative real-time imaging of K+ dynamics. GEPIIs as purified biosensors are suitable to directly and precisely quantify K+ levels in different body fluids and cell growth media. GEPIIs expressed in cells enable time-lapse and real-time recordings of global and local intracellular K+ signals. Hitherto unknown Ca2+ -triggered, organelle-specific K+ changes were detected in pancreatic beta cells. Recombinant GEPIIs also enabled visualization of extracellular K+ fluctuations in vivo with 2-photon microscopy. Therefore, GEPIIs are relevant for diverse K+ assays and open new avenues for live-cell K+ imaging. K+ plays an important role in physiology and disease, but the lack of high specificity K+ sensors limits our understanding of its spatiotemporal dynamics. Here the authors develop genetically-encoded FRET-based probes able to quantify K+ concentration in body fluids, cells and specific organelles.